Agroecological systems promoted by the Vicente Guerrero Group (GVG): Key factors for their permanence (Agro Productividad, 2025)
Objective: To determine the factors that ensure the permanence of agroecological activities and/or systems promoted among three family groups affiliated with the Vicente Guerrero Group (GVG).Design/methodology/approach: The research employed a mixed-methods approach, integrating qualitative techniques such as participant observation, interviews, and workshops with quantitative methods through a structured questionnaire. The survey was administered to 34 families from three different groups.Results: Key factors identified for the continuity of agroecological systems included regular field visits, the presence of a motivated local representative, the establishment of a demonstrative model plot, ongoing training, and the feasibility and adaptability of introduced innovations. To maintain their agroecological orientation, families implemented eight core practices: soil and water conservation, input reduction, polyculture systems, agroecological pest and disease management, efficient input use, crop rotation, field redesign, and on-site input production. Families expressed a strong interest in ongoing training related to agroecological innovations.Limitations on study/implications: The analysis focused solely on three of the 18 family groups connected to the GVG across Tlaxcala and Puebla, which may limit the generalizability of the findings.Findings/conclusions: The sustained success of agroecological initiatives requires dedicated efforts across all actors within the agroecosystem. The long-term adoption of promoted practices and systems hinges on shared commitments between the supporting organization (GVG) and the participating family groups.